2022
DOI: 10.31557/apjcp.2022.23.1.207
|View full text |Cite
|
Sign up to set email alerts
|

PARN Knockdown in Cell Lines Results in Differential and Cell-Specific Alterations in the Expression of Cancer-Associated mRNAs

Abstract: Ribonucleases (RNases) is the collective term used for the group of enzymes that are involved in mRNA degradation. The shortening of the poly (A) tail through deadenylation is the preferred mechanism of degradation of most eukaryotic mRNAs and poly (A)-specific ribonuclease (PARN) is the most important player in deadenylation. Besides its primarily role in mRNA stability, PARN is also involved in several non-conventional functions. It is conceivable that a decreased RNase activity can alter the stability of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In lung cancer, overexpression of CNOT6 predicts better patient survival outcomes, where patients with elevated CNOT6 expression are less likely to develop metastasis (Maragozidis et al 2015). PARN was reported to be downregulated in lung cancer cell lines, and PARN depletion does not impact proliferation of lung cancer cells (Babu et al 2022). However, it was found that PARN expression is upregulated, especially in young patients (Maragozidis et al 2015), suggesting that there are age-specific factors that contribute to the disease.…”
Section: Cancersmentioning
confidence: 99%
“…In lung cancer, overexpression of CNOT6 predicts better patient survival outcomes, where patients with elevated CNOT6 expression are less likely to develop metastasis (Maragozidis et al 2015). PARN was reported to be downregulated in lung cancer cell lines, and PARN depletion does not impact proliferation of lung cancer cells (Babu et al 2022). However, it was found that PARN expression is upregulated, especially in young patients (Maragozidis et al 2015), suggesting that there are age-specific factors that contribute to the disease.…”
Section: Cancersmentioning
confidence: 99%
“…The role of TP53 in mediating apoptosis of the primordial germ cells has been suggested as the possible mechanism in all-male phenotype in atm and fancl null zebrafish. Interestingly, we have shown that downregulation of PARN in cell lines reduces TP53 transcript levels 23 . Thus, it would be interesting to see if the TP53 pathway is responsible for impaired oogenesis in parn null mutants as seen in atm and fancl null mutants.…”
Section: Discussionmentioning
confidence: 88%
“…It is also found to be mutated in several diseases associated with telomere dysfunction and in genetic conditions involving bone marrow failures 9 , 20 , 21 . Also, our previous studies showed that PARN is consistently downregulated in non-small cell lung cancers 22 and PARN depletion in cell lines results in differential and cell-specific alterations in the expression of various tumor suppressor and oncogene mRNAs 23 . Given the fact that PARN is now considered a protein that has multiple roles in cells besides just mRNA stock clearing 5 , development of an alternative animal model to systematically examine the effects of complete loss of PARN was very much warranted as the previous attempt to generate Parn -null mice was unsuccessful 12 .…”
Section: Discussionmentioning
confidence: 90%